Analysis and Development of Framework for MIMO-GFDM System in Enhanced Mobile Broadband Scenario of 5G - Kalsotra, Surbhi (TIET, Patiala, 2025)
Now-a-days wireless communication systems are used in numerous applications, including smart cities, e-health services, smart agriculture, and the Internet of Things (IoT). The primary goal of the current fifth generation (5G) communication system is to support these services by ensuring higher data rates, enhanced efficiency, lower latency and ultra-reliable connectivity. To fulfil these stringent requirements, various waveforms have been proposed for current and future generations, like generalized frequency division multiplexing (GFDM), orthogonal time frequency space (OTFS), etc. These waveforms can be combined with multi input multi output (MIMO) systems, which improve system performance by providing both diversity and multiplexing gain. This dissertation presents an analytical framework for MIMO-GFDM systems, which in cludes the study of space-time coding (STC)-aided GFDM systems and their various sub blocks. Using this framework, the performance of the MIMO-GFDM system is thoroughly assessed. The second major contribution is a unique method for evaluating the system per formance, enabling error rate calculations for any fading channel through generalized expres sions. The third contribution focuses on the performance enhancement of the MIMO-GFDM system by using a precoder. The fourth aspect investigates the effect of channel impairments on the performance of MIMO-GFDM systems. These impairments are generated due to the unavailability of perfect channel state information. The fifth contribution is the evaluation of the MIMO-GFDM system for 5G enhanced mobile broadband (eMBB) scenario. Analytical results are validated through Monte Carlo simulations
Keywords: 5G; MIMO; Bit Error Rate; Symbol Error Rate; Space Time Coding; GFDM; eMBB; OFDM